(untitled) (Global Journal of Science Frontier Research, 2014)
Feeding time and regimen have the potentials to influence the performance of broiler breeder flocks and are thus of great importance. A literature review is presented concerning the responses of broiler breeders to feeding time and feeding regimen. There is a potential improvement in shell quality, egg weight and egg production that results from feeding later in the day ( afternoon feeding )or from splitting daily feed allocation (split feeding). Broiler breeders are usually given a limited daily feed allowance in the morning. This practice does not supply nutrients to coincide with the hen’s need.